-3(n-3)-(-5n-2)=n

Simple and best practice solution for -3(n-3)-(-5n-2)=n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(n-3)-(-5n-2)=n equation:


-3(n-3)-(-5n-2)=n

We simplify the equation to the form, which is simple to understand
-3(n-3)-(-5n-2)=n

Reorder the terms in parentheses
+(-3n+9)-(-5n-2)=n

Remove unnecessary parentheses
-3n+9-(-5n-2+)=+n

Remove unnecessary parentheses
-3n+9+5n+2=n

We move all terms containing n to the left and all other terms to the right.
-3n+5n-1n=-9-2

We simplify left and right side of the equation.
+1n=-11

We divide both sides of the equation by 1 to get n.
n=-11

See similar equations:

| 6x+3(x-10)=61-(x-1) | | (x-2)*(x-3)*(x-4)*(x-5)=360 | | 7/9(0.8) | | 16+19+x=56 | | 4x5/12 | | (14+10i)+(-4-18i)=0 | | 287=7(1-6n) | | 5x-5=85 | | 1-9(4d-2)-6d= | | 2x+y=(-6) | | 6.20x+5.60=5.10x+4.20 | | 4x+2y=176 | | 2y+2z=16 | | 16+19+x=19 | | 4x-5=85 | | -5x-2x=8-4+2x+1 | | (25b-6)-6(4b+1)=-2 | | 4g(16+2g)=8g+12 | | 3x+1.4=2x+23 | | -2(9-7x)-2(x-1)=8x | | (5v+6)(5v-5)= | | 5(5x+7)=3(8x+6)-5 | | x-21=61 | | (2x+5)(6x-1)=90 | | 3/4x+1/3=3/4(x+8) | | 9x^2+16y^2+6x+8y=2 | | 18=0.6(x+10) | | 16=m-4 | | 4.20x+5.60=6.20x+5.10 | | 5x/6x-5y/6y | | sin^2x+2sinx-3= | | x+(x*0.095)=55.82 |

Equations solver categories